El desarrollo psicomotriz en la enseñanza-aprendizaje de Cultura Física en los estudiantes de preparatoria de la Unidad Educativa Toacaso, en el período lectivo 2018-2019. - Quevedo Cajas, Olga Guadalupe (2019)
develop psychomotor in the teaching processes learning Physical Culture in preparatory children of the Toacaso Educative Unit?, for its process should be proposed as a general objective, the necessity to develop a programme of leisure activities for the psychomotor development of high school children in the Toacaso Educative Unit; in the methodological aspect the whole research process is based on the qualitative approach; and the development of non-experimental research because this is intended to improve the quality of learning; moreover the deductive method was used because it allows starting from theoretical, scientific generalities to establish relations with the particularity of psychomotricity and the object of investigation a basic method for systematizing the theoretical framework; as well as the inductive method, because it allowed us to relate the theoretical bases with the data obtained from the observation sheets, it constituted an important support in the analysis and interpretation of results; the techniques that were adapted to the investigative requirements with their respective instruments are the observation sheet; as general conclusions it is noted that: he structured proposal has been subjected to a validation process by experts and users who mostly place it at an excellent level, these results allow us to consider that; the methodological proposal of the proposal